2017
DOI: 10.1155/2017/6482842
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-LepRb Expressed in Gastric Cancer Patients and Related to Cancer-Related Depression

Abstract: Depression is the most common psychiatric disorder among cancer patients. Studies have not only highlighted that leptin and its receptor (LepRb) are independent poor prognostic factors in gastric cancer (GC) patients but also shown that the leptin-LepRb is necessary for antidepressant-like behaviors. In this study, we examined the serum and tissue leptin-LepRb expression in GC patients. Enzyme-linked immunosorbent assay showed that depressive GC patients had significantly higher serum leptin-LepRb than healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Additionally, cancer-related depression can be evoked by cancer-independent mechanisms due to the impact of cancer diagnosis and stress [123]. Another probable mechanism, responsible for the development of cancer-related depression, is the upregulation of the leptin receptor, as observed in the gastric tissue of depressive gastric cancer patients, demonstrating that leptin may be involved in the pathogenesis of cancer-associated depression [124].…”
Section: Major Depression Disorder (Mdd)mentioning
confidence: 99%
“…Additionally, cancer-related depression can be evoked by cancer-independent mechanisms due to the impact of cancer diagnosis and stress [123]. Another probable mechanism, responsible for the development of cancer-related depression, is the upregulation of the leptin receptor, as observed in the gastric tissue of depressive gastric cancer patients, demonstrating that leptin may be involved in the pathogenesis of cancer-associated depression [124].…”
Section: Major Depression Disorder (Mdd)mentioning
confidence: 99%
“…SIRT1 and phosphoinositide 3-kinase (PI3K), for instance, are activated in both GC and depression [16, 18]. In our previous work, we found that ABL1 was upregulated in patients with both GC/colorectal carcinoma and depression [19, 20], and some kinds of cytokines like Leptin-LepRb and COX2 are abnormally expressed [21, 22]. Given the role of ROS in depression, GC, and crosstalk with inflammation, we speculated that ROS, ABL1, and inflammation are involved in the development of GC as well as GC-related depression.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al published a clinical trial reporting that both serum and tissue leptin-LepRb are higher in depressive than in non-depressed patients with GC ( 41 ). Leptin is a hormone primarily produced in white adipose tissue and secreted into the plasma.…”
Section: Discussionmentioning
confidence: 99%